The effects of aloe vera gel addition on the effectiveness of sunscreen lotion - Tri Yuni Hendrawati; Hana Ambarwati; Ratri Ariatmi Nugrahani; Susanty; Ummul Habibah Hasyim (Jurnal Rekayasa Proses, 2020)
especially in cosmetics. The aloe plant that is cultivated in Indonesia to supply this industry is Aloe chinensis Baker. This research is to determine the effects of Aloe vera gel extract on the effectiveness of sunscreen lotion. The steps taken included Aloe vera gel extraction, flavonoid absorption test, sun protection factor (SPF) value measurement, pH test, viscosity test, homogeneity test, and organoleptic evaluation. The extract was added to the base sunscreen formulation at five different concentrations. UV-Vis spectrophotometry at 290 – 320 nm was performed on the preparations to determine their SPF values. The highest SPF value of 10.21 was found in the preparation containing 20% Aloe vera gel extract. This value falls within the national industrial standard for sunscreen SPF value range of 2 – 60. The research showed that a higher concentration of Aloe vera gel extract increased the pH, with the most elevated pH at 7.0 for the preparation containing 20% Aloe gel vera extract. This value also falls within the national pH standard for sunscreen of 4.5 – 8.0. The higher concentration of Aloe vera gel extract also increased the dispersive amount of the sunscreen preparation, with the highest value of 5 cm resulting from 20% Aloe vera gel extract addition. This research showed that the increased addition of Aloe vera gel extract resulted in higher SPF value.